The Political Economy of Popular Democracy - Morales Jr., Horacio (Kasarinlan: Philippine Journal of Third World Studies, 2007)
Understanding the interplay of political and economic forces both internal and external, is important to lead to the appropriate directions which could be taken by the Philippines to achieve development. The current transition stage shows symptoms of a political economic crisis as a result of the contradictions between the traditional and progressive political forces, mainly those who espouse elite democracy and popular democracy. The different political forces which are part of the popular democratic alliance are either those who subscribe to the capitalist or the socialist development framework. Looking at the practical factors, the state of the Philippine economy and international economic situation together with the theoretical factors of capitalist and socialist framework, the best way to reconcile the contradictions would be through the transition approach. This approach calls for historically-specific policies that reflect inherited conditions, including the level of development of the class struggle and external constraints on development. Pragmatically the government tries to mediate in the economic recovery but once recovery comes, the market regains free rein. The best alternative against the reactionary tide would be popular democracy and the political economy of popular democracy gives the most viable solution to the current economic crisis.
Keywords: popular democracy; political economy; economy